Pengaruh Persepsi Kualitas Terhadap Keputusan Pembelian Konsumen Pada Keripik Pedas Maicih - Thomas Djulianto Lie; Daru Purnomo; Dewi Kartika Sari (Cakrawala Jurnal Penelitian Sosial, 2017)
Maicih spicy chips is one of the brand that concern in food area. Start from UKM (Usaha Kecil Menengah), now Maicih product has been sold in International market. This research aim to understand the influence perceived quality on purchase decisions of the Maicih spicy chips. Population taken from Instagram follower’s @infomaicih which amount to 9.984 followers. The sample is calculated using Slovin formula the result is 385 peoples with purposive sampling technique. Data type that used in this research was quantitative data, data source that used is primary data and secondary. The research result show that perceived quality have significant influenced on purchase decisions showed from r count value 0,773 , proving correlation value so strong (>0,750) with significant level 0,000 > 0,05. Big influence percieved quality on purchase decision of the Maicih spicy chips from Adjusted R Square of 59% and the rest influenced by other variable outside this research.